ANALISIS STRATEGI PERSONAL SELLING DALAM MENINGKATKAN JUMLAH PENERIMAAN MAHASISWA BARU DI STIKES ABDI NUSANTARA - Eriza, Putri Ulfa; Paramitadewi, Punkie (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze personal selling strategies to increase new student admissions at STIKes Abdi Nusantara using a qualitative approach through data collection techniques such as interviews, observations, and document studies. The results indicate that personal selling strategies are implemented through various approaches such as school visits, WhatsApp communication, participation in campus fairs, and the involvement of lecturers, staff, active students, and alumni, which create two-way communication and build emotional bonds with prospective students. This strategy has had a positive impact on increasing the number of applicants, a success supported by the responsiveness of the promotion team, the use of appropriate media, and testimonials from alumni. Despite obstacles such as limited promotional staff and low initial response from prospective students, the institution is able to adapt its strategy adaptively, thus making personal selling an effective and relevant higher education promotion strategy.